The multiple mediating effects of illness perceptions and coping strategies on the relationship between physical symptoms and depressive symptoms in patients with heart failure. (February 2020) - Chen, Cancan; Fang, Wenjie; An, Yan; Wang, Lyu; Fan, Xiuzhen
Background: Depressive symptoms are prevalent and cause poor health outcomes in patients with heart failure. Studies show that the physical symptoms of heart failure are associated with depressive symptoms. However, little is known about the underlying mechanisms of this relationship. Aims: The purpose of our study was to examine the associations between physical symptoms, illness perceptions, coping strategies and depressive symptoms and to test the multiple mediation effects of illness perceptions and coping strategies on the relationship between physical symptoms and depressive symptoms in patients with heart failure. Methods: Physical symptoms, illness perceptions, coping strategies and depressive symptoms were assessed using self-reported questionnaires among 302 patients (64.2±11.9 years, 54% male) with heart failure in a tertiary general hospital. A serial multiple mediation model was tested using the PROCESS macro for SPSS. Results: Depressive symptoms were positively correlated with physical symptoms ( r =0.487, p <0.01), illness perceptions ( r =0.499, p <0.01) and acceptance–resignation coping ( r =0.580, p <0.01). The relationship between physical symptoms and depressive symptoms was mediated by illness perceptions (indirect effect: 0.036, confidence interval (0.014, 0.059)) and by acceptance-resignation (indirect effect: 0.034, confidence interval (0.019, 0.053)), respectively, and by these two in serial (indirect effect: 0.021, confidence interval (0.013, 0.033)). Conclusion: Patients with heart failure who have more physical symptoms are vulnerable to the development of depression. Healthcare providers should implement interventions focused on changing illness perceptions and reducing acceptance–resignation coping to relieve depressive symptoms.